PENGEMBANGAN MODEL PENGENALAN AIR UNTUK ANAK USIA DINI - Hernawan, Hernawan; Widiastuti, Widiastuti; Timur, Aprilia Intan; Pradityana, Karisdha (Program Studi Magister Pendidikan Anak Usia Dini, 2018)
The purpose of this research and development is to produce a model of water recognition for early childhood. The Subject in this research and develompent were students of Ikal I Kindergarten, At-Taubah Islamic Kindergarten, and Raudhatul Athfal Quraini Kindergarten aged 4-7. The Research method used is research and development with Barg and Gall Model. The data collection technique used is the result of expert validation and effectiveness test Through experiments with statistical data analysis paired t-test. The Result of the research and development of water reconition models for early childhood shows that, 1) the model of water recognition for early childhood significantly increasec that intial ability of children in swimming, 2) the result of validation test by swimming experts show that 25 items of model are feasible to be applied in the process of water recognition for early childhood, 3) the fffectiveness model of water recognition for early childhood is shown by the result of the childs pre-test and post-test obtained t-value 21.67 is greater than t-table and sig (2-tailed)< 0.005 . This means that there is an increise between before and after the treatment. Keyword: Development, Water Introduction, Early Childhood Tujuan penelitian dan pengembangan ini adalah untuk menghasilkan model pengenalan air untuk anak usia dini. Subyek dalam penelitian dan pengembangan ini adalah siswa TK I ikal I, TK Islam At-Taubah dan Raudhatul Athfal-Qur’ani yang beumur 4-7 tahun. Metode penelitian yang digunakan adalah penelitian dan pengembangan dengan model Barg and Gall. Teknik pengumpulan data yang digunakan adalah hasil validasi pakar dan uji efektivitas melalui eksperimen dengan analisis data statistik paired t-test. Hasil penelitian dan pengembangan model pengenalan air untuk anak usia dini menunjukkan bahwa (1) model peneganalan air untuk anak usia dini signifikan meningkatkan kemampuan awal anak dalam berenang, (2) hasil uji validasi oleh ahli renang menunjukan bahwa 25 item model layak untuk diterapkan dalam proses pengenalan air untuk anak usia dini, (3) keefektifan model pengenalan air ditunjukkan dengan hasil pre-test dan post-test anak diperoleh hasil t-hitung 21.67 lebih besar dari t-tabel, serta Sig (2-tailed) < 0.05 (α). Artinya terdapat peningkatan antara sebelum dan sesudah adanya treatment. Kata kunci: Pengembangan, Pengenalan Air, Anak Usia Dini